Effectiveness of Sexual Counseling on Sexuality of Cancer Patients: A Systematic Review - Rudi Nugraha; Yati Afiyanti; Hening Pujasari; Dewi Gayatri (Babali Nursing Research)
Introduction: Cancer patient care is a complex and ongoing process. The impact of cancer diagnosis and treatment on sexual quality is an important issue in cancer quality of life. Sexual counselling is one of the interventions chosen in handling sexual problems in cancer patients. This review aims to examine the effectiveness of sexual counselling on the sexuality of cancer patients.